Analisis Dan Perancangan User Interface Pada Website Indokafire Menggunakan Metode Heuristic Evaluation - Triswari, Citra Adjeng; Sulistiowati, Sulistiowati; Sudarmaningtyas, Pantjawati (Jurnal Sistem Informasi Universitas Dinamika (JSIKA), 2021)
PT. Indoka Putra Mandiri is a company located in Surabaya, and is one of the companies engaged in the manufacturing and retail of fire safety products. Based on the results of the initial questionnaire distribution with a sample of 20 respondents, it was found that more than 55% of respondents answered disagree with the variables that refer to the initial appearance of the website. Therefore, the solution offered is to design the user interface on the Indokafire website. In this study to design a user interface with the google design sprint model. To complete this research, it is divided into 3 stages, namely the initial stage, the development stage, and the final stage. The initial stage is the understand stage, which includes interviews with company owners and customers. Furthermore, benchmark data is made to compare the Indokafire website with other websites related to the sale of fire extinguishers. The diverge stage contains a record of any deficiencies on the website, after which an alternative design will be made. Furthermore, at the development stage, namely the decide stage, which is the stage to select one of the eight design alternatives that have been made. The chosen design alternative will be made a storyboard and continued at the next stage, namely the prototype stage. The last stage is the validate stage, the evaluation stage with the heuristic evaluation method. The results of the evaluation show that 20 respondents overall get a percentage of 100% agree and strongly agree with the new design.